The diagnosis and management of rare cystic liver metastases from nasopharyngeal carcinoma: A case report. Issue 26 (June 2018) - Liu, Qiuxia; Wang, Jianfang; Sun, Caiping; Xu, Jun
Abstract: Rational: Nasopharyngeal carcinoma (NPC) with cystic liver metastases is so rarely observed that there are only three cases reported in the published literature. Patient concerns: We present a case of NPC that received complete response after chemotherapy and definitive radiotherapy, but a liver cystic lesion was revealed on abdominal sonogram three months after the initial therapy. The cystic liver lesion initially resembled a simple liver cyst with fast growth, and then evolved into an abscess-like mass after a short term. Though abscess drainage was performed, and the mass shrank significantly, but it returned to previous size two months later. Diagnoses: Surgical resection was administrated both for diagnosis and treatment, and eventually the lesion was histologically demonstrated to be a liver metastasis. Eight months after the partial hepatectomy, cystic liver metastases recurred on computed tomography (CT) scan. Interventions: Though palliative systematic chemotherapy including paclitaxel, cisplatin, gemcitabine, navobine and anti-epidemal growth factor receptor (anti-EGFR) molecular-targeted therapy were performed, the cystic metastases still gradually progressed. Then Transcatheter Hepatic Artery Chemoembolization (TACE) was administrated for five times, and all the lesions were obviously decreased in size. Outcomes: After TACE treatment, the liver metastases maintained stable for six months, but lung metastases were noted. Finally, the patient died of liver failure. Lessons: The rare cystic appearance may be a special form which exists for liver metastases of NPC, indicating poor prognosis. Oncologists need to enhance the recognition and diagnosis level of this type of metastases. Intense follow-up and early diagnosis are important. While emphasizing the importance of local therapy and personal principles for liver metastases, TACE may be a preferred method for unresectable cystic liver metastases from NPC.